2002
DOI: 10.1046/j.1524-475x.2002.10703.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of PROMOGRAN, a protease modulating matrix, for the treatment of diabetic foot ulcers

Abstract: Proteases play a critical role in many of the physiologic processes of wound repair. However, if their activity becomes uncontrolled proteases can mediate devastating tissue damage and consequently they have been implicated in chronic wound pathophysiology. Previous studies have shown that chronic wound fluid contains elevated protease levels that have deleterious effects, degrading de novo granulation tissue and endogenous biologically active proteins such as growth factors and cytokines. Therefore, we have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 49 publications
6
167
0
8
Order By: Relevance
“…Among these factors are 2 classes of enzymes, whose levels are known to be elevated in chronic wounds: the matrix metalloproteinases (MMPs) 10 and elastase. 2 MMPs are implicated in proteolytic degradation of native intact collagen and partially degraded fragments of collagens. The dynamic creation and destruction of collagen components are normal events in acute wound healing, and MMPs also have a role to play in normal metabolic processes in the skin.…”
Section: The Role Of Collagen and Use In Chronic Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors are 2 classes of enzymes, whose levels are known to be elevated in chronic wounds: the matrix metalloproteinases (MMPs) 10 and elastase. 2 MMPs are implicated in proteolytic degradation of native intact collagen and partially degraded fragments of collagens. The dynamic creation and destruction of collagen components are normal events in acute wound healing, and MMPs also have a role to play in normal metabolic processes in the skin.…”
Section: The Role Of Collagen and Use In Chronic Woundsmentioning
confidence: 99%
“…Oxidized regenerated cellulose, a plant-based material, has been combined with collagen to produce a dressing capable of binding to and protecting growth factors by binding and inactivating matrix metalloproteinases in the wound environment. 2 The increased understanding of the biochemical processes involved in chronic wound healing allows the design of wound care products aimed at correcting imbalances in the wound microenvironment. Traditional advanced wound care products tend to address the wound's macroenvironment, including moist wound environment control, fluid management, and controlled transpiration of wound fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study, Cullen et al (98) reported that elastase and plasmin activities in wound fluids were significantly reduced by a local therapy with the protease inhibitor dressing, Promogran. Further studies (99,100) reported a trend to more frequent and rapid healing of diabetic foot ulcers and venous ulcers with these protease inhibitors.…”
Section: Local Therapy With Protease Inhibitorsmentioning
confidence: 99%
“…Oxidized regenerated cellulose/collagen matrix (ORC/collagen matrix) has been reported to improve the wound microenvironment by adsorbing wound exudate and retaining proteases within the dressing structure. [7][8][9][10][11][12][13] A randomized controlled trial demonstrated the superiority on modulating proteases of a wound dressing based on the LipidoColloid Technology, impregnated with a NanoOligo Saccharide Factor compared with an ORC/ collagen matrix. 14 A systematic review of the clinical evidence on protease-modulating dressing and researches that compare these devices would be useful in providing an overview of the appropriate treatment to achieve optimal healing for chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Among these, negative pressure therapy (NPT) plays an interesting role. NPT is a noninvasive therapy system that applies controlled negative pressure using a vacuum-assisted closure device.…”
Section: Introductionmentioning
confidence: 99%